Anti-HMGCR antibodies in systemic sclerosis. Issue 44 (November 2016) - Hudson, Marie; Luck, Yael; Stephenson, Mathew; Choi, May Y.; Wang, Mianbo; ,; Baron, Murray; Fritzler, Marvin J.
Abstract : Abstract: The objective of this study was to investigate the frequency of autoantibodies to hydroxymethylglutaryl coenzyme A reductase (HMGCR) in systemic sclerosis (SSc) and associations with inflammatory myositis and statin exposure. This was a cross-sectional, multicenter study of 306 subjects from the Canadian Scleroderma Research Group cohort who had complete data on statin exposure and serology for anti-HMGCR antibodies assayed by an addressable laser bead immunoassay (ALBIA). Descriptive statistics were used to summarize the baseline characteristics of the patients and to compare subjects with and without anti-HMGCR antibodies. Four (1.3%) subjects had anti-HMGCR antibodies. None of the subjects with anti-HMGCR antibodies titers had a history of an inflammatory myositis or overlap with polymyositis/dermatomyositis, compared to 8.6% and 2.0% of those without anti-HMGCR antibodies, respectively. In addition, none of the subjects with anti-HMGCR antibodies had past or current exposure to statins compared to 12% of those with negative titers. Anti-HMGCR antibodies are rare in SSc and are not associated with inflammatory myopathy or statin exposure. Larger studies will be required to confirm these preliminary observations. Nevertheless, we conclude that anti-HMGCR antibodies are unlikely to play a major role in inflammatory myopathy in SSc and anti-HMGCR antibodies can be present in subjects without exposure to statins.